1988
DOI: 10.1007/bf00146818
|View full text |Cite
|
Sign up to set email alerts
|

High cell density perfusion culture of hybridoma cells recycling high molecular weight components

Abstract: We have developed a high cell density and high product concentration culture system recycling high molecular weight components. The production of monoclonal antibodies in high concentration was performed by this culture system with mouse human hybridoma H2 and V6 cells in serum-free defined media.The concentration of IgG after 48 days culture of H2 cells in ITES-eRDF reached 2 mg/ml and the purity of IgG in culture fluid was 61%. In addition, high molecular weight components in serum-free media, such as transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 13 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…As can be seen in eq 2, the overall productivity, per bioreactor volume used, would be increased correspondingly. It has been previously reported that some hybridoma cell lines are growth phase-dependent with respect to the specific antibody production, while others are growth phase-independent (Suzuki and Olis, 1990;Takazawa et al, 1988); our work here indicates that the presence of antigen can shifi a cell line from one type to the other. This antigen-induced shift was also observed in proteinfree media (Dandulakis et al, 1994).…”
Section: Resultssupporting
confidence: 62%
“…As can be seen in eq 2, the overall productivity, per bioreactor volume used, would be increased correspondingly. It has been previously reported that some hybridoma cell lines are growth phase-dependent with respect to the specific antibody production, while others are growth phase-independent (Suzuki and Olis, 1990;Takazawa et al, 1988); our work here indicates that the presence of antigen can shifi a cell line from one type to the other. This antigen-induced shift was also observed in proteinfree media (Dandulakis et al, 1994).…”
Section: Resultssupporting
confidence: 62%
“…These include encapsulation, hollow fibers, cells entrapped on polymer beads, cells attached to ceramic supports, and cells in dialysis reactors.',4,5,7.12,14T25. 32 Such systems maintain cells for long periods at very low growth rates and high cell density, conditions which increase specific immunoglobulin secretion rates, to produce gram quantities of MCAB. However, the amount of MCAB produced is generally monitored by enzyme-linked immunosorbent assay (ELISA) in the culture supernatants, but the quality of MCAB produced as judged by its molecular integrity is rarely tested.…”
Section: Ntrod Uctlonmentioning
confidence: 99%
“…(a) Determination of the molecular weights of the 9.2.27 yza heavy and K light chains; 9.2.27 antibody was purified from cell culture supernatants with protein-A affinity chromatography, 10% reducing SDS gel. The molecular weight markers are myosin (H chain, 200,000), phosphorylase b (97,400), bovine serum albumin (68,000), ovalbumin (43,000), carbonic anhydrase (29,000) and P-lactoglobulin (18,400). (b) Fluorograph of a 10% reducing SDS gel of the MAb accumulated in the supernatant during the labeling period, for the cells collected in the stationary growth phase.…”
Section: Continuous Labeling Experimentsmentioning
confidence: 99%